A Hybrid Generator with Electromagnetic Transduction for Improving the Power Density of Triboelectric Nanogenerators and Scavenging Wind Energy. Issue 9 (7th April 2022) - Xin, Chuanfu; Guo, Hengyu; Shen, Fan; Peng, Yan; Xie, Shaorong; Li, Zhongjie; Zhang, Quan
Abstract: Due to the low output power of triboelectric nanogenerators (TENGs) in harvesting wind energy, this work proposes a hybridization scheme with electromagnetic generators (EMGs) to improve the power density of TENGs. Then, a novel configuration is designed and experiments of impedance matching and output power are conducted to compare the power density of triboelectric nanogenerators with/without electromagnetic generators under a wind speed of 5.5 m s −1 . According to the experimental results, the power density of the hybrid generator is 29.8 times higher than that of the triboelectric nanogenerator without electromagnetic generators (TENG‐WEMGs). To further demonstrate the output performance of the hybrid generator, experiments of charging capacitors and powering electronics are implemented at the same wind speed. Based on the experimental results, a capacitor of 2.2 mF is charged to 25.7 V within 20 s, 170 LEDs are lit, and the Bluetooth tracker is driven to transmit signals in real time. In addition, this work investigates the influences of different resistant loads of EMG on the average power of TENGs. This work can be of great significance to further develop self‐powered sensors. Abstract : This paper reports a hybridization scheme with electromagnetic generators to improve the power density of triboelectric nanogenerators. At a wind speed of 5.5 m s −1, the power density is increased 29.8 times, a capacitor of 2.2 mF is charged to 25.7 V within 20 s, 170 LEDs are lit, and the Bluetooth tracker is driven to transmit signals in real time.